2004
DOI: 10.1074/jbc.m400482200
|View full text |Cite
|
Sign up to set email alerts
|

The Polo Box Is Required for Multiple Functions of Plx1 in Mitosis

Abstract: Polo-like kinases comprise a family of evolutionarily conserved serine/threonine protein kinases that play multiple roles in cell cycle regulation. In addition to the N-terminal catalytic domain, polo-like kinases have one or two highly conserved C-terminal non-catalytic regions, termed polo boxes. These motifs are required for targeting these kinases to subcellular mitotic structures. Here we report that kinase-dead Xenopus pololike kinase (Plx1NA) functions as a competitor of endogenous Plx1 for polo box bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 60 publications
(89 reference statements)
4
39
0
Order By: Relevance
“…In supporting this direct model, the fission yeast Polo-like kinase, Plo1, has been demonstrated to interact directly with Cut23 (Apc8), a subunit of the APC/C (May et al, 2002). Moreover, Plx1 coimmunoprecipitates with the Xenopus APC/C in a PBD-dependent manner, although a direct interaction has not been established (Liu et al, 2004).…”
Section: Exit From Mitosismentioning
confidence: 86%
See 2 more Smart Citations
“…In supporting this direct model, the fission yeast Polo-like kinase, Plo1, has been demonstrated to interact directly with Cut23 (Apc8), a subunit of the APC/C (May et al, 2002). Moreover, Plx1 coimmunoprecipitates with the Xenopus APC/C in a PBD-dependent manner, although a direct interaction has not been established (Liu et al, 2004).…”
Section: Exit From Mitosismentioning
confidence: 86%
“…This highly synchronized oocyte maturation process provides an ideal system to study Cdc25C activation. It was found that upon PG treatment, Plx1 activation is concurrent with Cdc25C and Cdc2/cyclin B activation, and injection of Plx1 facilitated the activation of both Cdc25C and Cdc2/ cyclin B compared to that in buffer-injected oocytes, whereas injection of kinase-dead Plx1 (N172) or affinitypurified anti-Plx1 antibody significantly delayed their activation (Qian et al, 1998a;Liu et al, 2004). The inhibitory effect of Plx1 antibody was overcome by injection of wild-type, but not phosphatase-inactive Cdc25C, indicating that Plx1 is upstream of Cdc25C (Qian et al, 1998a).…”
Section: Phosphorylation Of Cdc25cmentioning
confidence: 99%
See 1 more Smart Citation
“…Fittingly, Emi1 is required to maintain the meiotic arrest in Xenopus egg extracts , suggesting a plausible explanation for the involvement of Plx1 in release from this arrest. Recent work by Liu et al (2004) showed that inhibition of meiotic exit by dominant negative Plx1 can be almost entirely relieved by addition of excess Cdc20 -the same treatment that relieves the inhibition of meiotic exit by excess Emi1. This again suggests that Plk1 does not significantly regulate the intrinsic activity of the APC, but instead regulates some upstream aspect of Cdc20 function.…”
Section: Activating the Anaphase Promoting Complexmentioning
confidence: 99%
“…Topics covered in this issue include functions of Plks in yeast (Lee et al), Drosophila (Glover), Xenopus (Liu and Maller), and mammals (Seeburg et al; Swallow et al; Myer et al). Since Plks possess the unique Polo box domain, the structure of which is critical for their function (Elia et al, 2003b;Liu et al, 2004), a specific chapter is devoted to the structure and function of Plks (Lowery et al, 2004). In more highly evolved animals, Plks have been shown to play an essential role in controlling cell proliferation, genomic stability, and oncogenesis.…”
Section: Introductionmentioning
confidence: 99%